Community Perception and Participation Towards the Conservation of Sowang Wood (Xanthostemon Novaguineensis ) in the Nyei Toro Pasir 6 Educational and Training Forest, Revenirara District, Jayapura Regency - ELisabeth Payung Allo; Inggrid Nortalia Kailola; Jeslin Inru Kufla (Jurnal Info Sains : Informatika dan Sains, 2026)
One of the natural resources that is endemic to Papua and is very potential is sowang wood which has many functions and benefits, namely: ecological functions, economic and socio-cultural benefits. This study aims to determine the factors related to community perception and participation in the preservation of sowang wood. The study was conducted in the Nyei Toro Pasir 6 Educational Forest, Ravenirara District, Jayapura Regency. Samples were taken by means of. . Community perception in the preservation of sowang wood as an ecological function is very good. Community feeling safe from landslides, the breeding of various types of wild animals, the availability of water, and as a construction for making houses on the sea and lakes, especially for the people in Jayapura Regency. The level of community participation in planting sowang wood is low. From the results of interviews and questionnaires for (1) the number of dependents in the family is very  a large relationship with perceptions of the ecological function in preserving sowang wood, while age, education and low income have a large relationship with community perception. (2) The number of family dependents has a large relationship with participation in planting sowang wood, while age, education and low income have a small relationship. (3) The level of community perception does not have a large relationship with the level of participation in preserving sowang wood.